Mulches from two tropical tree species Erythrina poeppigiana (Walpers) O.F. Cook and Gmelina arborea Rox. as nitrogen sources in the production of maize (Zea mays L.) - Quinlan, Mary M. (Universidad de Costa Rica (UCR), San José (Costa Rica) Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), 2014)
Tesis (Mag. Sc.) -- CATIE, Turrialba (Costa Rica) -- UCR, San José (Costa Rica), 1984